Knowledge and Data Sharing - Annual Technical Report 2022 - Ramírez, Margarita M.; Tanaka, Kenji; Castiblanco, Claudia; Pizo, Cristian; Tobon, Hector (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
As part of support the evidence-based decision-making, the main effort of this team is to ensure that integrity, quality, and value of research is appropriately managed at the cluster level. It also strengthens the culture of results-based project monitoring and evaluation (M&E) by ensuring the reporting of high-quality information products, based on the legal agreements is applied to AICCRA through the MIS reporting system called Managing Agricultural Research for Learning and Outcomes (MARLO).